Penerapan Metode Rapid Application Development (RAD) Dalam Perancangan Media Pembelajaran Multimedia - Ellbert Hutabri (Innovation in Research of Informatics (INNOVATICS), 2019)
Multimedia learning media is one of the learning media used in the teaching-learning process. Based on the results of observations made on simulation subjects and digital communication shows several obstacles in the learning process such as the level of student understanding of subject matter is still low, the level of student activity and the media used are still less varied because the learning process is still fixated with books and not available media multimedia learning in simulation subjects and digital communication. The method used is the RAD (Rapid Application Development) method with object oriented approach and uses UML as a tool for media development. Based on the results of the trial, the media designed can attract the attention of students when studying, and in hrapakan can increase student grades in simdig subjects.